PENGARUH PERSEPSI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PRODUK (Studi Pada Konsumen Minimarket Parabot Mart Sumbawa Besar) - Rosyidah Rachman; Abdul Rauf; Arsih Dianti Savina (Fakultas Ekonomi dan Manajemen, 2022)
This study aims to determine the effect of consumer perceptions on product purchasing decisions at the Parabot Mart Sumbawa Besar Minimarket. The type of data used in this study is quantitative data directly from research respondents through questionnaires. The ulation in this study is all consumers or customers who shop at the Parabot Mart Sumbawa Besar Minimarket whose number is not known with certainty. Considering that the population in this study is not known with certainty, the sampling in this study used a non-probability sampling approach with incidental sampling so that the sample in the study amounted to 100 respondents. Data collection in this study was carried out through a questionnaire or questionnaire. All data were processed using SPSS statistical processing software and analyzed using simple linear regression analysis techniques, partial hypothesis testing (t test), and determination coefficient test (R2). The results of this study indicate that consumer perceptions have a positive and significant effect on product purchasing decisions at the Parabot Mart Sumbawa Besar Minimarket. The degree of influence of consumer perceptions on product purchasing decisions at the Parabot Mart Sumbawa Besar Minimarket is 74.4%, while the remaining 25.6% is influenced by other variables beyond the reach of this research.